Answer: C
Step-by-step explanation: I took the quiz and they said it was correct
The square of a binomial expands as follows:
![(a+b)^2=a^2+2ab+b^2](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2)
Expanding all the binomials, we have
![4k^2-36k+81+k^2+4k+4=4k^2+4k+1+k^2-16k+64](https://tex.z-dn.net/?f=4k%5E2-36k%2B81%2Bk%5E2%2B4k%2B4%3D4k%5E2%2B4k%2B1%2Bk%5E2-16k%2B64)
Sum like terms:
![5k^2-32k+85=5k^2-12k+65](https://tex.z-dn.net/?f=5k%5E2-32k%2B85%3D5k%5E2-12k%2B65)
Simplify terms appearing on both sides:
![-32k+85=-12k+65](https://tex.z-dn.net/?f=-32k%2B85%3D-12k%2B65)
Move all terms involving k to the left and all numbers to the right:
![-20k=-20](https://tex.z-dn.net/?f=-20k%3D-20)
Divide both sides by -20:
![k=1](https://tex.z-dn.net/?f=k%3D1)
Answer:
A) y = -5/8x + 6
Step-by-step explanation:
y2 - y`1 / x2 - x1
7/2 - 11 / 4 - (-8)
-15/2 / 12
= -5/8
y = -5/8x + b
11 = -5/8(-8) + b
11 = 5 + b
6 = b
A = < 90°
the measure of the angle is less than 90